Examining the influence of error climate on aviation maintenance performance : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatu, New Zealand - Hodges, Megan Elizabeth (Massey University, 2011)
Error climate is a relatively new construct that refers to employees shared perceptions of organisational practices regarding errors and is divided into two types, error management climate (EMC) and error aversion climate (EAC). An EMC acknowledges the inevitability of error and has practices that deal effectively with error. An error aversion climate (EAC) conversely, denies error and is characterised by a fear of error and a reluctance to discuss error. The current study revealed two facets of EAC, these were error strain and covering up errors. EAC and EMC were negatively correlated. Higher levels of EMC were associated with better supervision and psychological health and lower levels of EAC, violations and errors. Higher levels of EAC were associated with the opposite pattern of findings, more violations and errors, worse psychological health, poorer supervision and lower levels of EMC. Two types of violations were found, situational violations which were related to getting the job done in the face of situational constraints and routine violations which reflected rule defiance. Significant predictors of situational violations were routine violations, covering up errors, stress, position (seniority) and general psychological health while significant predictors of routine violations were situational violations and fatigue. Significant predictors of errors were routine violations and position. The effect of error climate on errors was partially mediated by violations. This result is consistent with that of safety climate which is a well established predictor of unsafe acts. Unexpectedly, psychological health did not act as a mediator. These findings suggest that error climate is an important organisational factor in safety and aviation maintenance performance that warrants further examination.
Keywords: Aviation psychology; Aeroplanes; Maintenance and repair; Psychological aspects; New Zealand; Error climate; Aviation maintenance